1969
DOI: 10.1002/cpt1969101100
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of cigarette smoking on the hydroxylation of 3,4‐benzpyrene and the N‐demethylation of 3‐methyl‐4‐monomethylaminoazobenzene by enzymes in human placenta

Abstract: Cigarette smoking markedly increases the activity of enzymes in human placenta which hydroxylate 3,4‐benzpyrene and N‐demethylate 3‐methyl‐4‐monomethylaminoazobenzene. No detectable benzpyrene hydroxylase or aminoazo dye N‐demethylase activity was observed in 17 human placentas obtained after childbirth from nonsmokers, but these enzymes were found in the placentas obtained from 17 smokers. Considerable variability in benzpyrene hydroxylase activity was observed in placentas that were obtained from women who s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(41 citation statements)
references
References 7 publications
1
40
0
Order By: Relevance
“…c Activation reflects the fact that daily BaP treatment causes chronic AHR activation, which in turn leads to proliferation of the endoplasmic reticulum and increased liver weight and thymus weight; these effects are AHR-dependent but are independent of CYP1 metabolism (Uno et al, 2006). metabolism (Welch et al, 1968(Welch et al, , 1969Pantuck et al, 1972;Conney et al, 1976). Such human exposures to PAHs occur not only in the GI tract and lung but can also be important topically: PAH-induced AHH activity and BaP metabolic activation and detoxication are well known to occur in human skin (Alvares et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…c Activation reflects the fact that daily BaP treatment causes chronic AHR activation, which in turn leads to proliferation of the endoplasmic reticulum and increased liver weight and thymus weight; these effects are AHR-dependent but are independent of CYP1 metabolism (Uno et al, 2006). metabolism (Welch et al, 1968(Welch et al, , 1969Pantuck et al, 1972;Conney et al, 1976). Such human exposures to PAHs occur not only in the GI tract and lung but can also be important topically: PAH-induced AHH activity and BaP metabolic activation and detoxication are well known to occur in human skin (Alvares et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…The studies also established the induction of the CYP1A1 enzyme activity as a primary event in the formation of the trans-7,8-diol 9,10-epoxide of B[a]p. The consequence(s) of B[a]p bioactivation by CYP1A in cultured cells was best illustrated in the selection of B[a]p-resistant variants in hepa1c1c7 cells, a mouse hepatoma cell line that preserves many of the hepatocyte properties and is highly responsive to induction of CYP1A by PAH inducers (Whitlock, 1990;Hankinson, 1995 Analyses of the induction of AHH activity in human tissues or cultured human cells provided the initial observations of CYP1A induction in humans. Early studies by Conney and associates first revealed that AHH activity was detected in placentas obtained after birth from smoking mothers, but not from nonsmokers, consistent with an induction of CYP1A by PAHs present in tobacco smoke (Welch et al, 1969). However, AHH activities in placentas from mothers who smoke the same amount of cigarettes exhibit variations as large as 84-fold.…”
Section: Comparison Of Major B͓a͔p Responses In Vitro and In Vivomentioning
confidence: 94%
“…The AHH activity .in human placenta is extremely variable (33)(34)(35)(36)(37). Although its presence is dependent on maternal smoking, the extent of induction seems to be determined by genetic factors (36,38).…”
Section: Human Placentamentioning
confidence: 99%